Pengetahuan Mampu Meningkatkan Pemberian ASI Eksklusif pada Bayi di Pustu Golodukal - Madur, Junita P.; Kurniati, Kornelia; Murti, Nelviani (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Indonesia's exclusive breastfeeding coverage in 2022 was recorded at only 67.96%, down from 69.7% in 2021, indicating the need for more intensive support so that this coverage can increase. Not providing breast milk contributes to infant mortality due to poor nutritional status which affects the baby's health and survival. To determine the effect of knowledge on exclusive breastfeeding for 0-6 months in the Pustu Golodukal working area. This research is quantitative descriptive with a cross-sectional approach. Samples were taken using total sampling technique with a total of 28 people. The statistical test used was chi-square with the measuring tool for data collection being the questionnaire. Most mothers with good knowledge categories were able to provide exclusive breastfeeding to their babies from 0-6 months. Statistical tests prove the results of the p-value = 0.008. There is an influence between the mother's knowledge of the baby's behavior on exclusive breastfeeding for babies 0-6 months at Pustu Golodukal. Keywords: Breastfeeding Mothers, Knowledge, Exclusive Breastfeeding  ABSTRAK Cakupan ASI ekslusif Indonesia pada 2022 tercatat hanya 67,96%, turun dari 69,7% dari 2021, menandakan perlunya dukungan lebih intensif agar cakupan ini bisa meningkat.  Tidak memberikan ASI menyumbang angka kematian bayi karena buruknya status gizi yang berpengaruh pada kesehatan bayi dan kelangsungan hidup bayi. Untuk mengetahui pengaruh pengetahuan terhadap pemberian ASI eksklusif 0-6 bulan diwilayah kerja Pustu Golodukal. Penelitian ini adalah deskriptif    kuantitatif dengan   pendekatan   secara cross. Sampel diambil dengan tehnik Total sampling dengan jumlah 28 orang. Uji statistic yang digunakan menggunakan chi-square dengan alat ukur untuk pengumpulan data adalah kuiosner. Ibu dengan kategori pengetahuan yang baik Sebagian besar mampu memberikan asi eksklusif pada bayinya dari 0-6 bulan. uji statistic membuktikan hasil nilai p-value= 0,008. Ada pengaruh antara pengetahuan ibu bayi terhadap perilaku pemberian ASI eksklusif bayi 0-6 bulan di Pustu Golodukal. Kata Kunci: Ibu Menyusui, Pengetahuan, Pemberian ASI Eksklusif